RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN PERUMDA ANEKA USAHA PURWOREJO MENGGUNAKAN METODE SMART (SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE) BERBASIS WEBSITE - Mahasinul Akhlak, Muhammad Lutfi; Chalwani, Muhammad; Astuti, Dwi (STMIK BINA PATRIA, 2024)
The aim of the research is to design and build a Decision Support System for Employee Recruitment at Perumda Aneka Usaha Purworejo Using the SMART (Simple Multi Attribute Rating Technique) Method Based on a Website with the PHP programming language and MySQL database which can provide fast, precise and accurate information. The research methodology used is the Design Thinking method approach. Design thinking is a methodology carried out through deep understanding (insight) into customers or users to find solutions to problems or ideas for improvement opportunities. Design thinking consists of 5 stages, namely: exploration (empathize), identification (define), ideation (ideate), visualization (prototype) and evaluation (test). The design used in this research is a UML (Unified Modeling Language) construction. UML has graphic diagrams including use case diagrams, class diagrams, activity diagrams, sequence diagrams, and statechart diagrams. The results of user evaluation found that the average score obtained was 8.4 from the maximum average score of 10. The average score of 1.6 was not achieved because there was no automatic feature available to fill in the parameters and criteria so that the Employee Recruitment Decision Support System Perumda Aneka Usaha Purworejo Using the SMART Method (Simple Multi Attribute Rating Technique) can support HRD in making decisions in determining new employees for Perumda Aneka Usaha Purworejo more effectively, objectively and transparently.